Double-positive with positive anti-glomerular basement membrane antibody and ANCA-positive disease in a patient with dermatomyositis. (24th July 2018) - Dein, Eric J; Crespo-Bosque, Monica; Timlin, Homa; Geetha, Duvuru
Abstract : Approximately one in four patients (23.3%) with inflammatory myositis including dermatomyositis can require evaluation for acute kidney injury. The main cause of kidney injury is acute tubular necrosis from medications or myoglobinuria, though clinicians should be aware of a wide variety of possible aetiologies. We present the case of a 44-year-old woman with stable anti-Jo1 dermatomyositis, who presented with acute kidney injury. During her hospital course, she was diagnosed with double-positive disease characterised by circulating anti-glomerular basement membrane antibody and myeloperoxidase antineutrophil cytoplasmic antibody and renal biopsy revealing crescentic glomerulonephritis with linear staining of capillary wall for IgG.